PENGEMBANGAN FLASHCARD BERBASIS PANCASILA SEBAGAI MEDIA PEMBELAJARAN INTERAKTIF BAHASA INGGRIS PADA SISWA SEKOLAH DASAR - Tri Arie Bowo; Budiati Budiati (Faculty of Economics, Law, and Humanities, 2019)
English is pivotal in the globalization era since it is a bridge that connects one country with others. People from around the world able to interact directly using English as the medium of communication. The mastery of English is usually followed by its accompanying culture (western culture). Elementary school students who obtain English without internalizing Pancasila (Indonesia Ideology) values tend to think individually and ignoring their surroundings. If it is continuing, it will lead to national disintegration. Therefore, this research contributes to combine the values of Pancasila with English. Data collection methods were descriptive qualitative in the form of surveys, interviews, and observations. The research begins with the observations in bookstores and textbooks for elementary school students. the development of the model will begin with data collection. The pre-development stage is in the form of qualitative data by collecting primary data. Primary data collection was obtained from sample of elementary schools in Ungaran. The flashcard development process was designed with the Research and Development research design. Based on the data analysis, Pancasila-based flashcard consist of 50 cards divided into 5 types that based on the five principle of Pancasila. Those types are Religiosity, Humanity, Unity, Democracy, and Equality. Further research and dissemination are needed to perfect Pancasila-based flashcard.